FAKTOR-FAKTOR PENENTU STRATEGI MARKETING UNTUK MENINGKATKAN PENJUALAN PADA PERUSAHAAN ALAS FOTO PROPS - Tirtorahardjo, Darren; Marwan, Jubery; Utama, Zahera Mega (KELOLA: Jurnal Ilmiah Manajemen, 2025)
In a business environment, increasing sales is a priority for companies to maintain profitability and competitiveness. Adaptation and innovation are essential for success. Sales growth requires an understanding of market dynamics, consumer behavior, and industry trends. Implementing an effective marketing strategy is key, involving analysis, planning, implementation, and evaluation. Market research and analysis help companies identify opportunities to boost sales. Jerome McCarthy introduced the 4P marketing mix consisting of product, price, place, and promotion. Kotler and Keller later expanded it to 8P, adding people, process, physical evidence, and productivity. Other factors such as word of mouth, social media, and influencer. This study examines these 11 factors to analyze determining factors in marketing strategy that impact sales and to identify relevant factors to increase sales. Data was collected through questionnaires distributed to 130 respondents using random sampling. Data analysis was conducted using SPSS. The result indicate that price has t-value of 2.377 > t-table of 1.98, with a significance level of .019. Physical evidence has t-value of 2.384 > t-table of 1.98, with a significance level of .019. price has t-value of 2.279 > t-table of 1.98, with a significance level of .024